2000
DOI: 10.1002/clc.4960230206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early captopril therapy after myocardial infarction on the incidence of late potentials

Abstract: A " l S s. MANOLIS, M.D., FACC, FESCBackground: Late potentials (LP) on signal-averaged electrocardiography (SAECG), recorded 6 to 30 days after an acute myocardial infarction (AMI), identify patients at risk for late arrhythmic events. Angiotensin-converting enzyme (ACE) inhibitors have been shown to reduce ventricular remodeling and cardiovascular mortality after AMI. Results: In the two groups of patients there were no differences in mean values of SAECG parameters. No patient was receiving any antiarrhythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…AT1 receptor blockers prevent ventricular dilation, dysfunction, and cardiac hypertrophy in non-infarcted myocardial tissue following MI. Some of the effects observed in patients in the setting of baseline use of RAAS inhibition are related to decreased electrical irritability, which is due primarily to the well-established effects exerted by ARBs on remodeling and the preservation of LV systolic function [ 34 , 35 ]. Our study showed that valsartan ameliorates KCNJ2/Kir2.1 remodeling during the healing phase after MI when significant structural remodeling also accurs.…”
Section: Discussionmentioning
confidence: 99%
“…AT1 receptor blockers prevent ventricular dilation, dysfunction, and cardiac hypertrophy in non-infarcted myocardial tissue following MI. Some of the effects observed in patients in the setting of baseline use of RAAS inhibition are related to decreased electrical irritability, which is due primarily to the well-established effects exerted by ARBs on remodeling and the preservation of LV systolic function [ 34 , 35 ]. Our study showed that valsartan ameliorates KCNJ2/Kir2.1 remodeling during the healing phase after MI when significant structural remodeling also accurs.…”
Section: Discussionmentioning
confidence: 99%
“…3 The possible mechanisms suggested include a potassium-sparing effect, a sympatholytic effects, and an attenuation of ventricular remodeling by treatment with these agents that may lead to a reduced occurrence of ventricular arrhythmias. 6,7 Although ARBs have been less extensively evaluated, theoretically they may have "protective" effects similar to those of ACE inhibitors, but with better tolerability. 6,7 Although ARBs have been less extensively evaluated, theoretically they may have "protective" effects similar to those of ACE inhibitors, but with better tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, some studies have demonstrated that the arrhythmia substrate, manifesting as the presence of LP, was favorably influenced by ACEI treatment. 6,7 Although ARBs have been less extensively evaluated, theoretically they may have "protective" effects similar to those of ACE inhibitors, but with better tolerability. Animal models have shown that losartan and captopril increased the threshold of ventricular fibrillation, decreased mortality, and decreased episodes of ventricular tachycardia and ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Without doubt, major advances have been made in therapy for their control and prevention, with the development of pharmacologic and electrophysiological approaches including antiarrhythmic agents, beta-adrenergic drugs, catheter ablation, and the implantable cardioverter-defibrillator (ICD). In parallel, an added benefit of renin-angiotensin-aldosterone system (RAAS) blockers introduced for therapy of post-MI left ventricular (LV) remodeling and dysfunction, including the angiotensin II (AngII) type 1 receptor (AT 1 R) antagonists or blockers (ARBs), has been the suppression of VAs and sudden cardiac deaths (SCDs) as well as Bfinal^deaths and their contribution to improved survival and outcome [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…Increased AngII after MI and the arrhythmogenic effect of AngII acting via AT 1 R are well documented [6,[22][23][24]. The postulated mechanisms have centered around limitations of infarct size, adverse post-MI infarct zone and structural LV remodeling [6,18,24] and electrical remodeling [1][2][3][4][5][6][7]. Recent experimental studies with valsartan post MI documented decreased AT 1 R expression, decreased fibrosis and restored connexin43 in the border zone and reduced PES-induced VAs [25], and reduced transmural dispersion of repolarization and electrical heterogeneity with preserved the density of the outward potassium current (Ito) [26].…”
mentioning
confidence: 99%